Agronomic performance of peanut genotypes under minimum cultivation in the Triângulo Mineiro - Aparecido Filho, Antonio Carlos (2020)
It aimed to evaluate the agronomic performance of peanut genotypes under minimum cultivation in the Triângulo Mineiro. The trial was installed in a sugarcane renewal area, in minimal cultivation, in the 2019/20 agricultural year, in the Iturama-MG region. The experimental design used was in randomized blocks, containing four replicates and eight treatments: lines 18-2101 OL, 17-1253 OL, 18-2133 OL, 18-2136 OL, 18-1952 OL and cultivars BRS 421 OL, BRS 423 OL, BRS 425 OL, developed by Embrapa's Peanut Breeding Program. The plots were constituted by two lines of three meters in length, spacing between lines of ninety centimeters and an interval of three meters between plots. Severity of black spot, mass of 100 grains and pod yield were evaluated. The lowest severity of black spot was observed in the cultivars BRS 421 OL, BRS 423 OL and BRS 425 OL. The highest grain mass was observed in BRS 421 OL (81.8 g), with the other genotypes between 74.4 and 77.6 g. The most productive genotypes were 18-2101 OL, BRS 423 OL, 17-1253 OL, BRS 421 OL and 18-2133 OL.